Surface treatment and characterization of PMMA, PHEMA, and PHPMA - Lim, H; Lee, Y; Han, S; Cho, J; Kim, KJ (AMER INST PHYSICS, 2001)
Poly(methylmethacrylate) (PMMA), poly (2-hydroxyethyl methacrylate (PHEMA), and poly(2-hydroxypropyl methacrylate) (PHPMA) were modified to improve the wettability by two techniques: plasma and plasma source ion implantation. The modified surfaces were characterized to investigate the dependence of the modification and hydrophobic recovery on the polymer structure. The differences obtained under optimal experiment conditions among the polymers were interpreted in terms of their polymer structures including the glass transition temperature. The surface free energy, calculated from the contact angle measurements, revealed that its polar component was a dominant factor in improving the wettability. The PSII treatment created more functional groups on the surface and extensively modified the polymer layer than the plasma treatment. (C) 2001 American Vacuum Society.
Keywords: SOURCE ION-IMPLANTATION; TREATED POLYSTYRENE; PLASMA; POLYMERS; POLYPROPYLENE